Applying Structural Equation Model to Explore the Impact of Performance Management on Business Performance at Small and Medium Enterprises - Trang Nguyen Thi Thu; Phan Thanh Tam (Bright Publisher, 2026)
This study investigates how key organizational factors shape performance management and how performance management, in turn, enhances business performance among small and medium enterprises in Vietnam. The research aims to clarify the extent to which enterprise culture, internal communication, training and development, reward systems, and digital transformation influence managerial effectiveness and organizational outcomes. Building on strategic human resource management and organizational performance theories, the study develops and validates a structural model that integrates both human and technological dimensions of enterprise performance. A mixed-methods design was employed. The qualitative phase involved in-depth interviews with managers to refine the conceptual framework and contextualize measurement indicators. The quantitative phase surveyed 864 managers from small and medium enterprises across southern Vietnam to empirically test the model. Structural equation modeling was applied to examine the relationships among core organizational factors, performance management, and business performance, as well as the moderating effect of digital transformation. The findings show that training and development exert the most substantial positive influence on performance management, followed by reward systems, internal communication, and enterprise culture. Performance management significantly enhances business performance, confirming its role as a strategic mechanism that translates organizational capabilities into improved outcomes. Digital transformation directly improves business performance and enhances the impact of performance management by enabling real-time data use, transparency, and process efficiency. Overall, the study provides empirical evidence that strengthening human resource practices and integrating digital technologies are essential for improving performance management and fostering sustainable growth among Vietnamese small and medium enterprises. The results have important implications for managers and policymakers seeking to build performance-driven, digitally adaptive business environments in emerging economies.